Hugh Macmillan, Chris Hani: A Jacana Pocket Biography: Fresh insights into the life and death of a struggle icon (Historia, 2021)
Hugh Macmillan begins this pocket biography of the life of Thembisile Martin Hani, better known as Chris Hani, with his subject's death. For those familiar with the history of South Africa's transition from apartheid to democracy in the early 1990s, this choice is not surprising. Hani's assassination on 10 April 1993 outside his home in Boksburg was one of the most significant events of the period and as Macmillan notes, had the potential to derail the negotiation process and trigger a bloody civil war. Mandela's public address on primetime television that evening - in which he called for calm - emphasised Hani's remarkable ability to unify the nation in troubled times. His death also marked a major turning point in the negotiation process. Mandela, along with other key negotiators, such as Cyril Ramaphosa and Joe Slovo, urged the government to act with greater urgency and pushed for the date of the first democratic elections to be finalised in the aftermath of Hani's murder.